Pendampingan Dalam Mendesain Lembar Kerja Peserta Didik (LKPD) Merdeka Belajar menggunakan Konteks Tarian bagi Guru Sekolah Menengah (Jumat Pendidikan: Jurnal Pengabdian Masyarakat, 2024)
This community service activity aims to provide knowledge and skills to produce the design of the Free Learning Student Worksheet (LKPD). The methods used in this activity consist of preparation, implementation and evaluation. This activity was held at FKIP UNSRI with the participants being High School Teachers of Pagaralam City offline and online. The results of this activity show the enthusiasm of teachers who have produced LKPD using dance contexts. The understanding of the teacher after the implementation of mentoring activities shows that the teacher's response to the activities carried out is very good. Some math teachers, Indonesian, English have been able to design LKPD Merdeka Belajar based on pagaralam dance context.